How to be a better...decision maker - Barker, Alan (How to be a better., 1996)
This text offers step-by-step guidance on decision-making topics. Subjects covered include: ensuring individual decisions are part of a larger strategy; getting the timing right by avoiding leaping to early decisions and deciding too late; and measuring the success of the decision.